Gamification aspects affecting mobile app continued use, attitude, and satisfaction - Nugroho, Sahid Susilo (Jurnal Siasat Bisnis, 2024)
Purpose – The aim of this study is to shed light on the factors influencing continued use, attitude, and satisfaction with gamified mobile app usage. A research model is proposed, featuring achievement, social, confirmation, ease of use, enjoyment, recognition, and social influence as independent variables. Dependent variables encompass continued use, attitude, satisfaction, motivation, and usefulness. Design/methodology/approach – Data were collected from 1,633 respondents who use gamified shopping apps. Hypothesis testing was conducted using path analysis, and the Bootstrapping method was used to test the significance level of each relationship. Findings – Results indicate that achievement and social factors have a positive impact on motivation. Motivation, confirmation, and usefulness all positively influence satisfaction. Usefulness is shaped by confirmation and ease of use. Moreover, usefulness, ease of use, and social influence positively correlate with attitude and continued use. Contrarily, neither enjoyment nor recognition appeared to influence attitude or continued use. Research limitations/implications – This study did not incorporate frequency and personal traits into the model. While the results are particularly relevant to shopping apps, their applicability may extend beyond this context. Future research could consider frequency and personal characteristics as moderating variables and sample objects from varied industries. Practical implications – When developing gamification strategies, businesses ought to take into account both utilitarian and social aspects of gamification. It's vital to understand user expectations, prioritize user-friendly gamification interfaces, and promote positive word-of-mouth. Originality/value – This research enriches both the gamification and marketing literature by introducing a model grounded in gamification elements, human motivation theory, and the expectation-confirmation paradigm. It underscores the pivotal role of utilitarian and social facets in shaping usefulness, motivation, satisfaction, attitude, and continued app use. Notably, this work paves the way for further exploration into the roles of enjoyment and recognition.